2013
DOI: 10.15193/zntj/2013/86/070-080
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Lipids and Oxidative Changes Therein in Particularized Parts of Rainbow Trout Fillets

Abstract: GRZEGORZ BIENKIEWICZ, ZDZISŁAW DOMISZEWSKI, GRZEGORZ TOKARCZYK, DOMINIKA PLUST  ROZMIESZCZENIE LIPIDÓW I ICH ZMIANY OKSYDACYJNE W POSZCZEGÓLNYCH CZĘŚCIACH FILETÓW Z PSTRĄGA TĘCZOWEGOS t r e s z c z e n i e Lipidy ryb ze względu na swój charakter są bardzo podatne na utlenianie, szczególnie na procesy autooksydacji. Stopień utlenienia lipidów zależy od wielu czynników, w tym od ich rozmieszczenia w tkance mięśniowej.Celem pracy było wykazanie, że poszczególne części fileta z pstrąga tęczowego hodowlanego różni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…Subcutaneous and ventral lipids have dripped the fastest. The differences in the distribution of lipids in rainbow trout fillet and its various properties depending on the location were presented by Bienkiewicz et al. (2013) Barbosa et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subcutaneous and ventral lipids have dripped the fastest. The differences in the distribution of lipids in rainbow trout fillet and its various properties depending on the location were presented by Bienkiewicz et al. (2013) Barbosa et al.…”
Section: Resultsmentioning
confidence: 99%
“…Having characterized the trend of lipid changes (B-D-lipids) we observe a similar trend as it was the case of free lipids (Ch-lipids), but the dynamics of these changes is much smaller. One of the main factors of this difference is a different distribution of fish fat and its different susceptibility to oxidation (Bienkiewicz et al., 2013) as well as easier access and interaction of lipids (B-D-lipids) with antioxidant protein components. The study carried out by Serpen et al.…”
Section: Resultsmentioning
confidence: 99%
“…However, such fatty acids have proved to be especially prone to lipid oxidation development (Rustad, ), this leading to a wide range of negative effects on nutritional value (Undeland, ; Hes, ) and healthy concerns (Falade et al ., ; Vieira et al ., ). Therefore, previous research confirmed that an inhomogeneous distribution of lipid content and unsaturation degree in seafood may lead to a different damage development in the different parts of the product (Mørkøre et al ., ; Bienkiewicz et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, farmed fatty fish have a higher level of contamination compared to farmed lean fish [ 124 , 125 ]. In addition, the fat content within the fillet is not the same, which makes it difficult to compare the content of impurities if different parts of the fillet were analyzed, e.g., the dorsal or the abdominal [ 126 ]. Due to the fact that the content of contaminants in feed is strictly limited and controlled [ 127 ], this translates into a lower level of contamination in farmed fish.…”
Section: Seafood Safetymentioning
confidence: 99%